Wet Shotcrete Process Using a New Set of Small-Sized Equipment for Concreting Formless Computer Simulation - Emeljanova, Inga; Virchenko, Viktor; Chayka, Denys (International Journal of Engineering and Technology, 2018)
The article discusses the new all-purpose small equipment process usage. On example of the proposed equipment process analysis was maiden computer simulation. Basic machine determining dependences unevenness values are given - concrete pump hose and the value of its reliable operation. Full automation of wet shotcrete working process controlling algorithm developed.Â Â